The Roman Past of three Spanish Cities as the Impetus behind the Rise of Archaeological Tourism - Trinidad Tortosa; Carlos J. Morán (Culture & History Digital Journal, 2023)
The development of archaeology as a scientific discipline and its legislative regulation from the nineteenth century onwards have served as the framework for a series of interventions in the field of heritage. The recovery of monuments and testimonies of the past helped society to rediscover its roots, represented in certain iconic elements which in turn became symbols of identity. At the same time, the phenomenon of tourism emerged as a leisure activity associated, above all, with the enjoyment of the leisure time of the new bourgeoisie. The union of these two poles of interest, heritage and tourism, is therefore due to a demand from the society in which these activities take place. The study of the development of this phenomenon in Spain leads us to investigate three different cases: Carmona, Mérida and Tarragona, whose common link is the Hispano-Roman past. This paper analyses the confluences and particularities of these three paradigmatic enclaves in Hispanic archaeology, which are also exponents-and catalysts-of the birth and development of archaeological tourism.